104k views
5 votes
(1+√5)/(3+√5) Surs and need all working as I do not know how to do this at all

1 Answer

2 votes


= ((1 + √(5)) )/((3 + √(5)) ) \\


= ((1 + √(5)) )/((3 + √(5) )) * ((3 - √(5) ))/((3 - √(5)) ) \\


= \frac{1(3 - √(5)) + √(5) (3 - √(5) )}{ ({3})^(2) - { (√(5) })^(2) } \: \: [∵ {a}^(2) - {b}^(2) = (a + b)(a - b) ]\\


= (3 - √(5) + 3 √(5) - 5 )/(9 - 5) \\


= ( - 2 + 2 √(5) )/(4) \\


= (2( - 1 + √(5) ))/(4) \\


= ( - 1 + √(5) )/(2) \\


\large\mathfrak{{\pmb{\underline{\red{Mystique35 }}{\red{}}}}}

User PleasantD
by
5.7k points